A comparative meta-genomic analysis of HPV strains: A step towards the design, synthesis and characterization of noval quenazoline derivative for antiviral activity. (April 2018) - Dhanaraj, Premnath; Devadas, Akila; Muthiah, Indiraleka
Graphical abstract: Highlights: Computer aided drug design concept is proposed to solve biological problems. We modeled and synthesized chemical derivative with 93–95% purity. We performed computational docking and spectral analysis. We proposed a novel chemical molecule can be act as a good molecule. Various Computational genome and proteome analysis insight to predict new methodology for drug discovery. Abstract: Epigenetic characterization studies have clearly shown that the association of genital Human Papilloma Virus (HPV) with cervical cancer is strong, independent of other risk factors, and consistent in several countries. Even though all the strains of Human Papilloma Virus can cause cancer, the high-risk strains can cause severe cancer in a human. The E6 and E7 protein are responsible for the carcinogenic property of HPV. Among these two proteins, the HPV E7 protein plays a major role in the viral life cycle by allowing the virus to replicate in differentiating epithelial cells. All the strains of HPV are variants (High risk and low risk). A computational analysis study is done to find which low-risk strain is showing most similarity with the high risk there by predicting that this low-risk strain can be converted to high-risk if a mutation occurs in future. Through mutation, a normal strain will get converted to low-risk and a low-risk to high-risk. So the mutations are important and it can affect the viruses to a greater extent because of their smaller size. In order to inhibit the expression of Type 11 low-risk strain a noval suppressor molecule is synthesized and characterized using UV, FTIR and NMR spectrometry. The suppressor molecule is a quinazoline derivative, as it can act as an anti-cancer agent to inhibit the expression of the E7 protein in Type 11 strain. The efficiency of binding of type 11 E7 protein with quinazoline derivative is calculated through docking studies using G-Score (Schrodinger). Thus proposing this noval suppressor molecule can be lead against cervical cancer caused by HPV Type 11 strain after further in-vitro and in vivo characterization.